ONC213: a novel strategy to resensitize resistant AML cells to venetoclax through induction of mitochondrial stress - Jenna L. Carter; Yongwei Su; Eman T. Al-Antary; Jianlei Zhao; Xinan Qiao; Guan Wang; Holly Edwards; Lisa Polin; Juiwanna Kushner; Sijana H. Dzinic; Kathryn White; Steven A. Buck; et al. (Journal of Experimental & Clinical Cancer Research, 2025)
Abstract Background Venetoclax + azacitidine is a frontline treatment for older adult acute myeloid leukemia (AML) patients and a salvage therapy for relapsed/refractory patients who have been treated with intensive chemotherapy. While this is an important treatment option, many patients fail to achieve complete remission and of those that do, majority relapse. Leukemia stem cells (LSCs) are believed to be responsible for AML relapse and can be targeted through oxidative phosphorylation reduction. We previously reported that ONC213 disrupts oxidative phosphorylation and decreases Mcl-1 protein, which play a key role in venetoclax resistance. Here we investigated the antileukemic activity and underlying molecular mechanism of the combination of ONC213 + venetoclax against AML cells. Methods Flow cytometry was used to determine drug-induced apoptosis. Protein level changes were determined by western blot. An AML cell line-derived xenograft mouse model was used to determine the effects of ONC213 + venetoclax on survival. A patient-derived xenograft (PDX) mouse model was used to determine drug effects on CD45+/CD34+/CD38-/CD123 + cells. Colony formation assays were used to assess drug effects on AML progenitor cells. Mcl-1 and Bax/Bak knockdown and Mcl-1 overexpression were used to confirm their role in the mechanism of action. The effect of ONC213 + venetoclax on mitochondrial respiration was determined using a Seahorse bioanalyzer. Results ONC213 + venetoclax synergistically kills AML cells, including those resistant to venetoclax alone as well as venetoclax + azacitidine. The combination significantly reduced colony formation capacity of primary AML progenitors compared to the control and either treatment alone. Further, the combination prolonged survival in an AML cell line-derived xenograft model and significantly decreased LSCs in an AML PDX model. Conclusions ONC213 can resensitize VEN + AZA-resistant AML cells to venetoclax therapy and target LSCs ex vivo and in vivo.